2021
DOI: 10.1177/17531934211017703
|View full text |Cite
|
Sign up to set email alerts
|

Arthroplasty in the hand: what works and what doesn’t?

Abstract: This review describes the different possibilities for arthroplasties at the proximal interphalangeal joint, thumb carpometacarpal joint, distal radioulnar joint, metacarpophalangeal joint and the wrist. For each joint, the indication for arthroplasty is explained, the surgical technique with the suitable implant is described and a brief summary of the outcomes reported in the literature is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
4
0
1
Order By: Relevance
“…All patients needing revision presented with a dislocation of the implant, which in our opinion may be related to the instability inherently related to Pyrocardan®. In a series by Herren et al [ 21 ], authors reported a less favourable outcome after revision surgery as compared to primary trapeziectomy. Conversely, it should be emphasized that in our series, patients who undergone trapeziectomy reported clinical results overlapping those reported after primary trapeziectomy (18.3 points for DASH as compared to 17–34 points reported in a recent systematic review about trapeziectomy [ 22 ]).…”
Section: Discussionmentioning
confidence: 99%
“…All patients needing revision presented with a dislocation of the implant, which in our opinion may be related to the instability inherently related to Pyrocardan®. In a series by Herren et al [ 21 ], authors reported a less favourable outcome after revision surgery as compared to primary trapeziectomy. Conversely, it should be emphasized that in our series, patients who undergone trapeziectomy reported clinical results overlapping those reported after primary trapeziectomy (18.3 points for DASH as compared to 17–34 points reported in a recent systematic review about trapeziectomy [ 22 ]).…”
Section: Discussionmentioning
confidence: 99%
“…The capsule and sagittal band is repaired, and the extensor tendon is centralized if needed to prevent recurrent deformity. 3 Intrinsic release or transfer will help restore alignment and correct potential distal swan neck deformity.…”
Section: Surgical Approachmentioning
confidence: 99%
“…22 Additional studies found no difference in range of motion or complications between the dorsal and volar approaches. 3,23,24…”
Section: Surgical Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Arthroplasty of the hand, which involves the surgical removal and replacement of damaged cartilaginous surfaces in the joint, often emerges in many patients as the sole option for improving mobility and alleviating pain [214]. Typically requiring the use of an implant [215], this intervention particularly concerns the proxi-8. Towards a disruptive, minimally invasive small finger joint implant concept:…”
Section: Introductionmentioning
confidence: 99%